ADVANCES IN THALASSEMIA MANAGEMENT AND CHELATION THERAPY - Barbaros Şahin Karagün (Hematology, Transfusion and Cell Therapy)
Autosomal recessive thalassemias are a heterogeneous group of diseases characterized by hypochromic microcytic anemia, which develops as a result of defective synthesis of one or more of the hemoglobin (Hb) chains. It occurs when the Hb chain or chains are produced in small numbers or not at all. In other words, while the production of beta chains is insufficient, the production of alpha chains causes alpha thalassemia. Approximately 3 babies in every 1000 births in the world are affected by severe beta chain disorders, and approximately 350,000 new babies with the disease are born each year. Even under modern treatment conditions, severe clinical complications may develop in the clinical follow-up of patients.In recent years, the introduction of oral chelators and the ability to determine organ iron load with non-invasive methods have played a very important role in improving the prognosis of patients with thalassemia. Today, the only and definitive treatment option for cases with beta thalassemia major is hematopoietic stem cell transplantation. After myeloablative conditioning treatment, allogeneic stem cell transplantation from an HLA-compatible sibling donor is considered the treatment of choice. However, for patients who do not have a suitable donor, the risk of mortality and morbidity, especially in transplants from unrelated or haploidentical donors, creates anxiety.Therefore, in recent years, alternative gene therapy strategies have been studied that aim to correct the defective β-globin gene by transferring a normal β-globin gene or replacing the defective gene with homologous recombination. RNA-based treatment approaches, known as RNA Therapies, are also being investigated in the treatment of thalassemia. These treatments target the genetic mutations that cause thalassemia and aim to correct faulty RNA production.In addition to regular blood transfusions applied to improve the quality of life of patients, Iron Chelators are among the new drugs and treatment approaches in thalassemia patients. Iron binders used as part of thalassemia treatment help to remove iron accumulated in the body due to continuous blood transfusions. The most commonly used iron binders today include deferoxamine, deferasirox, and deferiprone. These drugs help prevent iron accumulation from causing damage to organs.New drugs used other than chelatorsHydroxyurea: Although hydroxyurea is usually used to treat sickle cell anemia, it is also being investigated in the treatment of thalassemia. This drug can relieve anemia symptoms by increasing hemoglobin production. In some thalassemia patients, hydroxyurea treatment can reduce the frequency of blood transfusions.Luspatercept: Luspatercept is a biologic drug that reduces the need for blood transfusions by increasing the production of red blood cells. This drug can improve the quality of life of patients by regulating the production of blood cells.Ferroportin Modulators: Ferroportin is a protein that plays an important role in iron transport in the body. New treatment strategies aim to reduce iron imbalance and excessive iron accumulation by modulating ferroportin. This treatment is among the future treatment options for controlling iron overload in thalassemia patients.Epoetin Alfa and Epoetin Beta: Epoetin alfa and epoetin beta are analogs of the hormone erythropoietin (EPO). These drugs may improve anemia management and reduce the frequency of blood transfusions in some thalassemia patients.Conclusion: Future treatment options include alternative treatment approaches such as genetic therapies, biologics, and bone marrow transplantation. Clinical studies are constantly being conducted on new treatment methods, which aim to further improve patients' response to treatment. These new drugs and treatment options used in the treatment of thalassemia aim to improve patients' quality of life and manage the symptoms of the disease. However, each patient's response to treatment may vary, so the treatment plan should be individualized for each patient. More research is needed on the effectiveness and safety of new treatment approaches.